ENTERAL FEEDING OF THE INFANTS AFTER CARDIOSURGICAL INTERVENTIONS - A.A. Diuzhikov; L.V. Zhivova; D.Yu. Kalabanov; D.A. Bombin; A.I. Kislitsky; N.I. Putilina (Вопросы современной педиатрии)
The nutrient support of the children after cardiosurgical interventions is currently reviewed as the most important factor in the complex of therapy, which is capable to prevent the catabolic trend of metabolism and risk for the development of the postsurgical complications. In this respect, in the cardiosurgery, high requirements for the nutritious mixtures are set during the enteral feeding. Such requirements are met by the specialized mixtures on the basis of the serum protein hydrolysates. The authors believe that the mixture of the choice may be Nestle's semi celemental mixture alfare.Key words: cardiosurgery, congenital heart disease, infants, enteral feeding.